DNA and lipid molecular stratigraphic records of haptophyte succession in the Black Sea during the Holocene - Coolen, Marco; Saenz, J.; Giosan, L.; Trowbridge, N.; Dimitrov, P.; Dimitrov, D.; Eglinton, T. (Elsevier BV, 2009)
Previous studies suggest that the coccolithophorid haptophyte Emiliania huxleyi entered the Black Sea ~ 3400 yrs ago and since then a coccolith ooze defined as Unit I has developed. Unit I sediments contain long-chain alkenones derived from E. huxleyi whereas the alkenone distribution of the deeper coccolith-free sapropel (Unit II) is rather unusual. Alkenone-derived past sea surface temperature (SST) estimates suggest a large difference between Unit II and Unit I, which is likely a result of unusual biological precursors of the alkenones in Unit II. Here, we report a high-resolution stratigraphic analysis of ancient haptophyte DNA to establish the Holocene succession of haptophytes as sources of the alkenones in the Black Sea. Haptophytes related to brackish Isochrysis spp. were the initial sources of alkenones, and appeared immediately after the onset of sapropel deposition (~ 7550 yrs before present [a BP]). As salinity increased, Isochrysis-related haptophytes were slowly replaced by a complex suite of E. huxleyi strains as sources of alkenones. Our paleogenetic data showed that E. huxleyi colonized the Black Sea shortly after the onset of sapropel deposition, ~ 4000 yrs earlier than previously recognized based on their preserved coccoliths. E. huxleyi strains were the most likely source of the previously reported abundant and unusual C36 di-unsaturated "Black Sea alkenone". Strong haptophyte species and strain-specific effects were observed on the level of unsaturation of alkenones which resulted in spurious alkenone-derived SST estimates before 5250 a BP. In contrast, from ~ 5250 a BP onwards a relatively stable haptophyte assemblage dominated by a different suite of E. huxleyi strains yielded robust alkenone-SST values and indicated a gradual cooling from 19 °C to ~ 15 °C at the top of the record (~ 450 a BP).